THE ROLE OF LINGUISTIC AND NON-DISCIPLINARY TOOLS IN COMMUNICATION MANAGEMENT (Scientific journal of the Fergana State University, 2024)
This article states that communicative behavior is a purely individual speech appearance of a person, naturally associated with the personal, national and social characteristics of the participants in the conversation. Any speech action is necessarily connected with the personality of the speaker or, in other words, any dialogue contributes to the actualization of the personal characteristics of its participants, that is, the personality and its psychological characteristics are revealed in the dialogue and determine its content and development. In the article, the theoretical points are presented using examples.